Intention to have a second child among Chinese women one year after the implementation of selective two-child policy: a cross-sectional survey. (October 2016) - Xu, Xianglong; Zuo, Hanxiao; Rao, Yunshuang; Zhang, Lei; Wang, Lian Lian; Zhao, Yong
Abstract: Background: The so-called selective two-child policy was introduced on December, 27, 2015 in China to allow Chinese couples nationwide to have up to two children if either parent is an only child. This study aims to explore Chinese women's intention to have a second child. Methods: We surveyed women from 16 hospitals in five Chinese provinces from June 1 to August 31, 2015. Multivariable logistic regression analysis was used to evaluate the sociodemographic factors related to seven key reasons for entering second pregnancy. All data analyses were performed using SAS (version 9.1). This study was approved by the Ethics Committee of the Chongqing Medical University. All participants submitted written informed consent. Findings: 2345 women were surveyed; we recruited 590 of these women who were pregnant with their second child for this study. The key reasons for entering second pregnancy among the studied women included: benefits for the first child 153/590 (26·1%), love of children 152 (25·8%), adoption of the two-child policy 68 (11·5%), concerns of losing the first child 44 (7·5%), suggestions from grandparents 44 (7·5%), sex of first child 15 (2·5%), and disability of the first child 8 (1·4%). Multivariable logistic regression showed that pregnant women whose current partner was not the father of their first child had less intention for a second child for the benefits of the older child than did mothers whose partner was the father of the older child (OR 0·33 [95% CI 0·13–0·84]). Parents without siblings were less likely to report having a second child because of love of children than parents who have siblings (women, 0·54 [0·36–0·81]; men, 0·56 [0·38–0·83]). Compared with Han Chinese women, women from minority backgrounds were 2·67 times more likely to have a second child because of the love of children (OR 2·67 [95% CI 1·18–6·04]). Women with higher education level were less likely to be influenced by their parents (0·13 [0·05–0·32]). Women with higher education level were more likely to be influenced by the selective two-child policy (3·185 [1·506–6·735]). Women without siblings and those living in urban areas were less likely to have a second child due to the concerns of losing the first child than those who had siblings (0·37 [0·17–0·81]) or lived in rural areas 0·518 [0·27–0·99]). Interpretation: Women who are better educated are more likely to have a second child to meet personal needs and the two-child policy seems to have less of a determining role. Having siblings, marital and paternity factors, and residency status also influence the decision to have a second child. Funding: Medjaden Academy & Research Foundation for Young Scientists (Grant No. MJR20150047 ) and Summer Social Practice Project of School of Public Health and Management, Chongqing Medical University.